Acculturation and Children’s Education in a Rural Adivasi Community - Mishra, Ramesh Chandra; Joshi, Shobhna (INDIAN EDUCATIONAL REVIEW, 2015)
The study focuses on the problems of education of the Kharwar Adivasi children in relation to acculturation taking place in the life of Kharwar people. Assessment was made of the level of acculturation that has taken place in salient domains of people’s life. Participants (N = 400) were interviewed and were also asked to rate the importance of a number of factors, which they considered responsible for a variety of educational processes, such as children’s attendance at school or their drop out, perceived value of education, needs beyond school education, perception of schooling and its contribution to the life of children, families and the community at large. The findings indicated family’s economic and social resources as more important reasons for children’s non-attendance of school relative to other factors, such as child’s interest or the cultural tradition of not going to school. The benefits of schooling were regarded as confined to “personal” level. Absence of teachers and lack of discipline in schools were regarded as highly frustrating aspects of schooling. The participants did recognise the possibilities of economic gains/employment and social recognition through schooling, but they reported schooling not really contributing much to this end.